2008
DOI: 10.1103/physrevb.78.245103
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectroscopy in CoO: Phononic, electric, and magnetic excitation spectrum within the charge-transfer gap

Abstract: The reflectivity of single-crystalline CoO has been studied by optical spectroscopy for wave numbers ranging from 100 to 28 000 cm −1 and for temperatures 8 Ͻ T Ͻ 325 K. A splitting of the cubic IR-active phonon mode on passing the antiferromagnetic phase transition at T N = 289 K has been observed. At low temperatures the splitting amounts to 15.0 cm −1 . In addition, we studied the splitting of the cubic crystal-field ground state of the Co 2+ ions due to spin-orbit coupling, a tetragonal crystal field, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 74 publications
9
39
0
Order By: Relevance
“…The coupling constant λ = −18.7 meV used here has been deduced from reflectivity measurements of CoO by optical spectroscopy. 22 The final term H a · S represents a small uniaxial anisotropy which defines the in-plane orientation of the moments and produces a spin gap at the Γ-point (and, equivalently, the M-point). We chose the moments to lie along the x axis, and to achieve this the anisotropy field H a points along +x on one of the antiferromagnetic sublattices and along −x on the other.…”
Section: Magnetism In Comentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling constant λ = −18.7 meV used here has been deduced from reflectivity measurements of CoO by optical spectroscopy. 22 The final term H a · S represents a small uniaxial anisotropy which defines the in-plane orientation of the moments and produces a spin gap at the Γ-point (and, equivalently, the M-point). We chose the moments to lie along the x axis, and to achieve this the anisotropy field H a points along +x on one of the antiferromagnetic sublattices and along −x on the other.…”
Section: Magnetism In Comentioning
confidence: 99%
“…For La 2 CoO 4 we include only the nearest-neighbour and next-nearestneighbour exchange interactions J, J 1 and J 2 , as defined in Fig These are estimated from a point-charge calculation and scaled to match the cubic crystal field splitting observed in CoO. 22 The parameter B 0 2 controls the out-of-plane anisotropy and was adjusted to obtain a good fit to the magnetic spectrum. Its final value (see below) differs from that deduced for La 1.5 Sr 0.5 CoO 4 by only ∼10%.…”
Section: Magnetism In Comentioning
confidence: 99%
“…1(c)]. In Fig.1(d) we plot the Néel temperatures of the TMMOs (MnO: T N = 118 K [20], Fe 0.92 O: T N ≈ 198 K [21,22], CoO: T N = 289 K [23,24], and NiO: T N = 523 K [25]) as a function of J 2 S(S + 1), using J 2 values from [26], and find a linear slope of k B T N /J 2 S(S + 1) ∼ 3 (solid line) close to the expected relation in mean-field approximation (dashed line). In a pioneering paper Massidda et al [6] showed that even for purely cubic TMMOs the antiferromagnetic order is accompanied by a Borneffective-charge redistribution from spherical to cylindrical with the antiferromagnetic axis being the symmetry axis, e.g.…”
mentioning
confidence: 99%
“…From the expressions for ε 3,4 and ε 5,6 one finds that at ϑ = ±π/2 the excited states are degenerate doublets, i.e., ε 3 = ε 5 and ε 4 = ε 6 . However, this choice of ϑ = ±π/2 cannot explain the observed splitting of the highest-lying doublet ε 4,6 which was observed by neutron scattering and optical spectroscopy.…”
mentioning
confidence: 99%
“…1 When contributions of the orbital moment and spin-orbit coupling are not negligible, a separation between spin and orbital degrees of freedom is not adequate anymore and the system is better described by an effective total angular momentum. 2,3 If spin-orbit coupling competes with electron-phonon or exchange interactions even strong fluctuation regimes can arise. [4][5][6] The system investigated here is the layered insulator Sr 2 VO 4 with tetragonal symmetry, which early on has come into focus as an isostructural d 1 analog of La 2 CuO 4 .…”
mentioning
confidence: 99%